2014
DOI: 10.1038/tpj.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

The c.480C>G polymorphism of hOCT1 influences imatinib clearance in patients affected by chronic myeloid leukemia

Abstract: The aim of the study was to investigate any possible influence of polymorphisms of transmembrane transporters human organic cation transporter 1 (hOCT1), ABCB1, ABCG2 on imatinib pharmacokinetics in 33 men and 27 women (median age and range, 56 and 27-79 years, respectively) affected by chronic myeloid leukemia. A population pharmacokinetic analysis was performed to investigate imatinib disposition in every patient and the role of transporter polymorphisms. Results showed that the α1-acid glycoprotein and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…When we analyzed the c.480 C>G hOCT1 polymorphism, we found that the wild-type CC genotype had a favorable impact on 36 months-EFS (87.5 vs 30% of individuals carrying the G allele; p = 0.04), hence confirming our previous results in this subset of patients [7]. In our series, 50% of cases showed a wild-type genotype.…”
Section: Predictive Value Of Pcgssupporting
confidence: 78%
See 2 more Smart Citations
“…When we analyzed the c.480 C>G hOCT1 polymorphism, we found that the wild-type CC genotype had a favorable impact on 36 months-EFS (87.5 vs 30% of individuals carrying the G allele; p = 0.04), hence confirming our previous results in this subset of patients [7]. In our series, 50% of cases showed a wild-type genotype.…”
Section: Predictive Value Of Pcgssupporting
confidence: 78%
“…The same analyses were performed in combination with hOCT1 genotyping, because our previous work demonstrated that the hOCT1 c.480C>G polymorphism significantly influences both drug disposition and event-free survival (EFS) [7]. Therefore, the inclusion of these variables within the analysis could improve the identification of possible markers of clinical outcome.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that GG+CG genotypes may be correlated with increased cellular exposure and increase risk of toxicities of Imatinib. 37 OCTN2 (SLC22A5) is another member of the SLC22 family of plasma membrane solute carrier proteins. 38 OCTN2 is expressed ubiquitously, with high expression in kidneys and lower expression in heart, skeletal muscles, and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients carrying a low-activity allele for uridine diphosphate glucuronosyl transferase may tolerate CPT-11 when the infusion rate is very low [68], despite this is not considered a standard regimen. Therefore, it is likely that the evaluation of drug concentrations (an endophenotype) in mathematical models may help in deciphering interindividual variability [35,69].…”
Section: Pharmacogenetic Profiling Of Mono-versus Poly-chemotherapiesmentioning
confidence: 99%